Design and Fabrication of Temperature‐Sensitive Nanogels with Controlled Drug Release Properties for Enhanced Photothermal Sterilization. Issue 72 (27th November 2017) - Li, Luoyuan; Fu, Limin; Ai, Xicheng; Zhang, Jianping; Zhou, Jing
Abstract: Invited for the cover of this issue is the groups of Limin Fu at the Renmin University of China and Jing Zhou at the Capital Normal University. The image depicts the bacteria being attacked by heat‐activated nanogel drug‐carriers. Read the full text of the article at 10.1002/chem.201702796 . Abstract : " when a red light is cast on them, the nanogels heat up, thereby acting as a trigger for drug release ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 18180 ff. (DOI:10.1002/chem.201702796 ).